Netflix en France ou la diversité de l’audiovisuel français face à la globalisation - Charles Marques (Bulletin de l’Association de Géographes Français)
Digital technologies deeply changed the way the audience thinks about TV shows, actually the most common kind of audiovisual practice. One of many symbols of this transformation is Netflix, a platform coming from Silicon Valley. Netflix is in a disruptive dynamic toward audiovisual, more specifically in France, where the practices of the platform are incompatible with the audiovisual regulations. This article shows the stakes of the implantation of Netflix in France, the way this American giant disturbed French audiovisual balance and the response of in place structures and finally the projects of industrials and politics to counter or cooperate with Netflix.